AN ANALYSIS OF LANGUAGE FUNCTION OF INDONESIAN THERAPEUTIC DISCOURSE: CUPPING THERAPY - Leony Mayang Seruni; Hamzah Hamzah (English Language and Literature, 2019)
The conversation in therapeutic is a kind of institutional discourse that have its own characteristic to make the communication. This research aims to find the language function in the Cupping conversation between the therapist and the patient. This research uses descriptive method. The data of this research are the the transcriptions of recorded conversation between the therapist and the patient. The sources of this data are the conversation from five therapist and each therapist have four patients. Hence, there are 20 conversation recorded in this research. The records of their conversations are transcribed as the data. The theory that used in this research is Leech (1974) to show language functions of the conversation. The result of this research shows that the conversation between the Cupping therapists and the patients have the tendency to used several forms of language functions. It is found that almost all conversations contained the informative language, directive language, and phatic language.